Quantifying the Impact of Wind and Surface Humidity‐Induced Surface Heat Exchange on the Circulation Shift in Response to Increased CO2. Issue 18 (22nd September 2020) - Tan, Zhihong; Shaw, Tiffany A.
Abstract: We extend the locking technique to separate the poleward shift of the atmospheric circulation in response to quadrupled CO2 into contributions from (1) CO2 increase, (2) cloud radiative effects, and (3) wind and surface humidity‐induced surface heat exchange. In aquaplanet simulations, wind and surface humidity‐induced surface heat exchange accounts for 30–60% of the Hadley cell edge and midlatitude eddy‐driven jet shift. The increase of surface specific humidity dominates and mostly follows global mean warming. Consistent with previous work the remaining shift is attributed to cloud radiative effects. Across CMIP5 models the intermodel variance in the austral winter circulation shift in response to quadrupled CO2 is significantly correlated with the response of the subtropical‐subpolar difference of surface heat exchange. The results highlight the dominant role of surface heat exchange for future circulation changes. Plain Language Summary: As climate warms, atmospheric wind patterns are predicted to shift poleward. However, climate models disagree on the magnitude of the shift, and we lack a clear understanding of the dominant mechanisms. Here we extend a technique that "locks" a given variable to quantify the importance of (1) CO2 increase, (2) cloud radiative changes, and (3) surface heat exchange changes. We apply the extended technique in a simplified Earth‐like model with global ocean to quantify the impacts of the three effects on the circulation shift in response to quadrupled CO2 concentration. In addition, we show that in response to a quadrupling of CO2 in 27 state‐of‐the‐art climate models, the model spread in the poleward shift of Southern Hemispheric wintertime circulation is significantly correlated with the response of the subtropical‐subpolar difference of surface heat exchange. Therefore, improving the understanding of surface heat exchange is important for improving the predictions of future wind patterns. Key Points: Extended locking technique quantifies the impact of wind and surface humidity‐induced surface heat exchange on the response to increased CO2 Surface humidity changes dominate surface heat exchange response and are as important as cloud radiative changes for circulation shift CMIP5 austral winter jet shift is correlated with subtropical‐subpolar contrasts in surface heat exchange